Розвиток акмеології: філософський аспект - Дерека, Тетяна; Dereka, Tаtiana (My University, 2016)
У статті проаналізовано філософські та педагогічні витоки акмеології. Визначено історичні та філософські передумови як провідні фактори становлення, формування та розвитку акмеології. Охарактеризовано акмеспрямовану філософію стародавності: первіснообщинний лад, Античність, період Середньовіччя. Визначено акмевершини з позиції трьох складових частин світоглядів: міфологічного; релігійного; наукового. Охарактеризовано період Середньовіччя з позиції релігійного світогляду на розвиток науки про людину та природу. Зазначено особливості передумов розвитку акмеології епохи Відродження, Нового часу, Просвітництва, епохи німецької класичної філософії. Визначено, що акмеологія як новий науковий напрям має основний принцип вершинності. Сучасний період формування акмеології характеризувався становленням акмеологічності розвитку людини (антропогенезу). Визначено етапи розвитку акмеології як наукового напряму. Проаналізовано передумови формування акмеології в Україні. Досягнення особистістю рівня акме передбачає такі «вчинкові кроки»: самопокладання як ціннісно-смислова екзистенційна творчість; самопотенціювання, самоопосередкування; самовизначення; самоактуалізація; самооцінювання; самоаперцепція; самозвертання.The article analyzes the philosophical and pedagogical origins of acmeology. There were historical and philosophical premises determined as a leading factors of acmeology becoming, formation and development. There were akme-oriented ancient philosophy characterized in the article, including primitive age, Antiquity, the Middle Ages. Acme-top is determined from the position of the three worldviews components such as mythological religious and scientific. The Middle Ages were characterized from the perspective of religious outlook on the man and nature sciences development. The features of the acmeology development prerequisites in Renaissance epoch, modern times, the Enlightenment, the era of classical German philosophy were specified. There were ideas of revival, reformation of the church together with socio-economic and technical changes affected the formation of the New Age acme-philosophy. It is determined that the Enlightenment the need of educational role of labor was understood due to a combination of person’s mental and moral development together with his labor skills formation. The German classical philosophy considered an acme to be a moral improvement of the individual, and it was seen from the perspective of morality being independent from religion influences. It is determined that acmeology as a new scientific field is based on the tops principle. The present period of the acmeology formation in Russia is characterized by the acmeo-emergence of man development (anthropogenesis) becoming and has three stages.The first stage (1928) is characterized by the introduction of the acmeology concept as the science of mature people development.
The acmeology development: philosophical aspect
Keywords: акмеологія; історичні передумови; етапи розвитку; acmeology; historical background; stages of development